OPINI MAHASISWA TERHADAP PELAKSANAAN KULIAH KERJA NYATA (KUKERTA) DI UNIVERSITAS RIAU - Lani, Ori Permata; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Field Work Experience (Kukerta) is intrakurikuler program with the main objective to provide education to students. The students of Field Work Experience (Kukerta) as a study conducted in the midst of the scientific community to implement possessed by every student of various disciplines, can then be applied in the middle of society. One of the institutions that implement activities Field Work Experience (Kukerta) is the University of Riau. The results showed that the student’s opinions is different, some refuse and support the implementation of Kukerta. The student’s opinions have mutual balance between supporting and rejecting.Key word : Communication, Opinion, Field Work Experience (Kukerta)